Implementation of Consumer Protection Policy in E-commerce Transactions in Indonesia - Wahyudiono, Tri; Fitria, Dewi Ulfa Lailatul; Husna, Asmaul; Merita, Rona (Pusat Studi Pembangunan dan Pemberdayaan, 2023)
Consumer protection in e-commerce is critical as the digital marketplace continues to expand rapidly in Indonesia. With the rise of online transactions, consumer rights are often threatened by fraudulent activities, unclear product descriptions, and inadequate dispute resolution mechanisms. This study aims to analyze the implementation of consumer protection policies in e-commerce transactions and assess their effectiveness. The research uses a normative juridical approach, focusing on legal frameworks such as the Consumer Protection Law No. 8 of 1999 and the Electronic Information and Transactions Law (UU ITE). The results indicate that while consumer protection laws are in place, enforcement remains weak, and many consumers are still unaware of their rights. Additionally, businesses often lack accountability in ensuring product quality and transparency. The study recommends strengthening the enforcement of consumer protection laws, improving public awareness, and enhancing the accountability of e-commerce platforms to ensure a safer digital marketplace for both consumers and businesses.